Impact of Neuropathic Pain on Health-Related Quality of Life and Disability in Patients with Chronic Low Back Pain - Bilge Kesikburun; Nihal Tezel; Nuray Gülgönül; Emel Ekşioğlu; Aytül Çakcı (Galenos Yayinevi, 2018)
Objective:Low back pain (LBP) is the most common chronic pain disorder worldwide. Chronic LBP is a mixed pain syndrome associated with nociceptive and neuropathic pain mechanisms. Investigation and early treatment of neuropathic pain is important in the management of chronic LBP. The aim of this study is to investigate the frequency of neuropathic pain and determine its impact on health-related quality of life and disability in patients with chronic LBP.Materials and Methods:A total of 120 patients with chronic LBP participated in the study. The presence of neuropathic pain was assessed using Leeds Assessment of Neuropathic Symptoms and Signs pain scale. 10-cm visual analogue scale (VAS) pain score, Oswestry Disability index (ODI) and short form-36 (SF-36) measurements were performed. Predictors for the presence of neuropathic pain were also investigated.Results:Neuropathic pain was detected in 49 (40.8%) of the patients with chronic LBP. ODI score and VAS pain score in patients with neuropathic pain were higher than that in those without neuropathic pain (p<0.001 and p=0.035, respectively). Physical function, body pain, general health and physical component subscales of SF-36 were lower in patients with neuropathic pain (p=0.043, p<0.001, p=0.012, p<0.001, respectively). Advanced age and radicular LBP were found as predictors for neuropathic pain (p=0.016 and p<0.001, respectively).Conclusion:The presence of neuropathic pain in chronic LBP was found relevant with poor health-related quality of life and disability. Advanced age and presence of radicular pain were associated with neuropathic involvement.